Studi Perbandingan Teknik Pembenihan Ikan Nila Jatimbulan (Oreochremis niloticus) Di Upt Kabupaten Bondowoso Jawa Timur - Muawanah Muawanah; Anjas Sasana Bahri; Sasanti Sihsubekti; Erik Ashar Eriyanto (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2026)
Based on FAO data (2010) cited by Khairuman and Amri (2008), the global market demand for fish was still experiencing a supply shortage of 2 million tons per year until 2010. This study discusses the comparison of Nile Tilapia (Oreochromis niloticus) breeding techniques between Jatimbulan at the Freshwater Aquaculture Development Unit in Pasuruan Regency and the Livestock and Fisheries Office in Bondowoso Regency. The aim is to determine the differences in Nile Tilapia breeding techniques between Jatimbulan at the Freshwater Aquaculture Development Unit in Pasuruan and the Livestock and Fisheries Office in Bondowoso, as well as to identify the best breeding methods to achieve superior breeding results, particularly in Nile Tilapia breeding. This research employs a comparative research method. The breeding techniques at the Freshwater Aquaculture Development Unit in Pasuruan and the Fisheries Office in Bondowoso both adhere to the Indonesian National Standard (SNI) for Nile Tilapia breeding techniques, SNI 7389:2017. The only difference lies in the facilities. The Freshwater Aquaculture Development Unit in Pasuruan has better water source facilities, larger pond sizes, and more extensive land. Therefore, the natural breeding technique for Nile Tilapia at the Freshwater Aquaculture Development Unit in Pasuruan is more effective in producing Nile Tilapia seeds with a higher survival rate